An intercellular pathway for glucose transport into mouse oocytes - Wang, Qiang (American Physiological Society, 2012)
Glucose is an essential nutrient for mammalian cells. Emerging evidence suggests that glucose within the oocyte regulates meiotic maturation. However, it remains controversial as to whether, and if so how, glucose enters oocytes within cumulus-oocyte complexes (COCs). We used a fluorescent glucose derivative (6-NBDG) to trace glucose transport within live mouse COCs and employed inhibitors of glucose transporters (GLUTs) and gap junction proteins to examine their distinct roles in glucose uptake by cumulus cells and the oocyte. We showed that fluorescent glucose enters both cumulus-enclosed and denuded oocytes. Treating COCs with GLUT inhibitors leads to simultaneous decreases in glucose uptake in cumulus cells and the surrounded oocyte but no effect on denuded oocytes. Pharmacological blockade of of gap junctions between the oocyte and cumulus cells significantly inhibited fluorescent glucose transport to oocytes. Moreover, we find that both in vivo hyperglycemic environment and in vitro high-glucose culture increase free glucose levels in oocytes via gap junctional channels. These findings reveal an intercellular pathway for glucose transport into oocytes: glucose is taken up by cumulus cells via the GLUT system and then transferred into the oocyte through gap junctions. This intercellular pathway may partly mediate the effects of high-glucose condition on oocyte quality.